Maternity protections: a review of part ix of the Employment Act 1955 / Liyana Zawani Mohd Radzi, Maizatul Fara’in Abdul Rahim and Manisah Saharin - Mohd Radzi, Liyana Zawani; Abdul Rahim, Maizatul Fara’in; Saharin, Manisah (2007)
This research is conducted for reviewing maternity protection given under Part DC of the Employment Act 1955. This topic is chosen for the reason that it had been issues of discussion on several grounds such as the period of maternity leave, the limitation on maternity allowances, paternity leave and family leave in private sector. Observations from various perspectives in order to support the finding of this research can be found in the first chapter until the fourth chapter. The finding of this research is seemed to favour the employee after taken all considerations regarding maternity protection in our country is still inadequate. Therefore, the last chapter will be concluded with the several proposed amendments and new laws that are recommended to be implemented under the Act for the future benefits.